Doing more with less - How frugal innovations can contribute to improving healthcare systems. (August 2022) - Sarkar, Soumodip; Mateus, Sara
Abstract: The dominance of an innovation discourse laden with cutting edge and expensive technologies, may be preventing us from recognizing alternative and complementary perspectives, which could help cut healthcare costs while improving worldwide access to health services. One such complementary approach is that of frugal innovation. Frugal innovation, as a way to produce efficacious and affordable products using fewer resources to reach the underserved customers, has received increasing attention in the social sciences literature. Although frugal innovation is commonly associated with emerging economies, there is now a rising interest from healthcare providers in developed countries, to find and apply effective, and lower-cost solutions. Nonetheless, knowledge on frugal innovation and its role in healthcare is dispersed across different literatures which hampers researchers and practitioners to access a fuller, and integrated picture of the phenomenon. In this study, by synthesizing extant knowledge, we tackle the fragmentation of the phenomenon. We elucidate on who the actors are, what is being done, how are such innovations being developed, and what the outcomes are, providing a framework that lays out the underlying mechanisms of frugal innovation in healthcare (FIH). The midrange theory that we develop, provides a conceptual framework for researchers to undertake empirical observation and models to guide managerial practices. Furthermore, by providing a more unified perspective of frugal innovation in healthcare, we hope to initiate conversations on the development, adequacy and adoption of these innovations in healthcare services, which could increase affordability and access for the population while maintaining quality. Highlights: Frugal innovation's contribution towards the improvement of healthcare systems. Tackling global health inequalities by providing low-cost but efficacious solutions. Describing antecedents, processes, and outcomes of frugal innovation in healthcare.